Condom Use Behavior Among The Customers of Transgender Sex Workers (Case Study At Kendal District) (Public Health Perspective Journal, 2018)
During 2013, Graha Mitra NGO showed that 44 transgender involved in transgender organization in Kendal Perwaka have been reached by the Field Officer. During the period of one year 10 transgender were stated positive through monthly STI screening at Kaliwungu Health Center. Outreach data in 2014 showed that the number of affordable transgender became 38 transgender and 17 of them were STI positive. In 2015 the outreach of transgender in Kendal District reached 39 people and 17 of them were STI positive (Graha Mitra NGO, 2015). This study aims to obtain data on the basis on condom use behavior of the customers of transgender sex worker. This study used a qualitative approach, with in depth interview method towards transgender customers as the informants. The skill of using condom was still very low with various confidence levels in using condoms. Permanent couples, peers and the families of transgender clients did not influence the condom use behavior of transgender customers. Perwaka regulates condom use on its members since it was established, provided condoms in Cebongan. The community of transgender in Cebongan was able to do STI prevention and prevention activities. Condom use behavior in customers concluded that the condom use was consistent, but the responsibility for using condoms was low. This study was conducted to create a new program in the effort to overcome STI to a customer group.